How do incumbents respond to the threat of entry? evidence from major airlines - Goolsbee, Austan 1969-; Syverson, Chad (National Bureau of Economic Research, 2005)
"This paper examines how incumbents respond to the threat of entry of competitors, as distinguished from their response to competitors' actual entry. It uses a case study from the passenger airline industry--specifically, the evolution of Southwest Airlines' route network--to identify particular routes where the probability of future entry rises abruptly. When Southwest begins operating in airports on both sides of a route but not the route itself, this dramatically raises the chance they will start flying that route in the near future. We examine the pricing of the incumbents on threatened routes in the period surrounding such events. We find that incumbents cut fares significantly when threatened by Southwest's entry into their routes. This is true even after controlling in several ways for airport-specific operating costs. The response of incumbents seems to be limited only to the threatened route itself, and not to routes out of nearby competitor airports where Southwest does not operate (e.g., fares drop on routes from Chicago Midway but not Chicago O'Hare). The largest responses appear to be restricted to routes that were concentrated beforehand. Incumbents do experience short-run increases in their passenger loads concurrent with these fare cuts. This is consistent with theories implying incumbents will try to generate some longer-term loyalty among current customers before the entry of a new competitor. We examine evidence relating this demand-building motive to frequent flyer programs and find suggestive evidence in favor of this notion. There is only weak evidence that incumbents increase capacity on the routes"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Airlines -- Economic aspects; Competition -- Econometric models